The Role of Rose Essential Oil Aroma on the Learning Behaviorus: An Experimental Study - Köse, Evren; Sarsılmaz, Mustafa; Ögetürk, Murat; Kuş, İlter; Kavaklı, Ahmet; Zararsız, İsmail (Fırat University, 2007)
Objectives: The effects of rose oil aroma on the learning of rats were investigated. Material and Methods: The study was carried out on male Wistar rats. For this purpose, primarily labyrinth test was applied to 14 rats. After training period, passing duration was recorded of the rats that were habituated to labyrinth for finding the food which is in target compartment for 8 days. Then, the rats were randomly selected, divided into experimental and control groups, and then experimented by aroma test in the labyrinth. During aroma test, while the rats in the control group were kept under normal atmosphere conditions, the rats in the experimental group were exposed to rose oil aroma. Labyrinth test was performed to rats of all groups through experiment duration for 8 days. Results: The experimental group needed shorter period for finding the food in the target than control group. Conclusion: It was determined that the rose essential oil has effects on learning and memory. ©2007, Firat University, Medical Faculty

Giriş: Gül yağı aromasının sıçanların öğrenme davranışları üzerine etkisi araştırıldı. Gereç ve Yöntem: Bu çalışma Wistar cinsi erkek sıçanlar üzerinde yapıldı. Bu amaçla 14 adet hayvana labirent testi uygulandı. Deneme periyodundan sonra, 8 gün boyunca sıçanların hedef bölmeye konan yiyeceği bulmak için harcadıkları süre kaydedildi. Daha sonra hayvanlar rasgele deney ve kontrol grubu olarak ikiye ayrıldı. Kontrol grubu normal atmosfer şartlarında bırakılırken, deney grubundaki sıçanlar gül yağı aromasına maruz kaldılar. Labirent testi 8 gün boyunca her iki gruba tekrar yapılarak, süreler kaydedildi. Bulgular: Deney grubundaki hayvanlar hedefi bulmak için, kontrol grubuna göre daha kısa süreye ihtiyaç duydukları tespit edildi. Sonuç: Gül yağı aromasının öğrenme ve hafıza üzerine etkisi olduğu tespit edildi. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Öğrenme Davranışlarında Gül Esans Yağ Aromasının Rolü: Deneysel Bir Çalışma